Pengelompokan Daerah Padat Penduduk Untuk Penentuan Kawasan Perumahan di Kota Lhokseumawe Menggunakan K-Medoids Clustering - Rozzi Kesuma Dinata, Furqan, Sujacka Retno (LPPM-UNIKI, 2023)
Lhokseumawe city is one of the cities in Aceh province which has the second largest population after the city of Banda Aceh. With an area of ​​181.06 KM2 the population in Lhoseumawe reached 207.2 thousand in 2019. K-medoids on the population density clustering system in the city of Lhokseumawe is an application for clustering population density with very dense, dense and not dense clusters, with total data from 68 villages in the city of Lhokseumawe from 2017 to 2021. This research uses data mining techniques in the data management process using the K-medoids clustering method.